Motivation to Read? Reading among the Upper-Class Children in Finland during the 17th and 18th Centuries - Laine, Tuija (Knygotyra, 2021)
In the early modern Finland, the Catechisms were the only literature intended for children. Otherwise, the children from all classes had to read adults’ literature. Finland was a part of Sweden until 1809 and the reading of Swedish literature was possible especially among the upper classes and even the common people in the Swedish-speaking western coast. Three case studies of Finnish upper-class children from the 17th and the 18th centuries tell us about children’s reading habits, attitudes to reading and reading motivation in this situation. Richard M. Ryan’s & Edward L. Deci’s theory of self-determination has been used as a theoretical basis for this study. It highlights the combination of three basic psychological needs as means to motivation: autonomy, competence and relatedness.Autonomy was the most limited during the 17th century and emerged step by step towards the end of the 18th century. Relatedness would depend on circumstances in the family. If the family led an active social life, it would also reflect in the reading habits of the household members. All the children in this research belonged to the upper class, so they could read, and they studied diligently. Therefore, they felt competence. The relatives exhorted them in studying, which still increased their self-confidence. Motivation was mostly external at the beginning, but in some cases it gradually grew towards internal motivation. According to these cases, upper-class girls were freer to read what they liked than boys. Comparing to boys they were less educated, but at the same time they experienced less pressure to make progress in literary reading. If the domestic duties permitted, they would be able to use their free time for reading fiction. Boys had to concentrate on thinking about their future careers and subjects relevant to that.
Keywords: reading; children; motivation; early modern period; upper classes